Digital Literacy in Nutrition and Epidemiology: A Study of Madrasah Ibtidaiyah Students in Semarang Regency - Widajanti, Laksmi; Sutingsih, Dwi; Nur Faizah, Putri; Muftih, Amalia; Nurus Sholihah, Nadia; Ocktalifa Chumair, Nisrina (Indonesian Journal of Human Nutrition, 2024)
Digital literacy in nutrition and epidemiology point out to students’ competencies in using digital media to access and understand information on nutrition and epidemiology. This study aimed to analyze digital literacy in nutrition and epidemiology among students of Madrasah Ibtidaiyah in Semarang Regency. The research was conducted in seven months and included 60 MI students as participants. A quasi-experimental design was used, involving an intervention with a Digital Literacy in Nutrition Book and a Digital Literacy in Epidemiology Book for stunting prevention. Students’ knowledge and attitude scores were categorized as poor (<50), sufficient (50-69), and good (70-100). The Wilcoxon test was to analyzed data. Average knowledge scores before and after the intervention were 74.17 ± 10.58 and 73.25 ± 10.81, respectively, and attitude scores were 90.67 ± 12.05 and 83.17 ± 22.51. There was no significant distinction in knowledge before and after the intervention (Z = 0.414; p=0.679), but there was a significant variation in attitude (Z=2.528; p=0.011). Conclusion, although students’ average literacy in digital nutrition and epidemiology slightly decreased, the changes in knowledge and attitudes were not statistically significant.